Perubahan Perilaku Menyampah Siswa Melalui “Reinforcement” - Vanda Ningrum; Deshinta Vibriyanti; Inayah Hidayati; Intan Adhi Perdana Putri; Luh Kitty Katherina; Sari Seftiani (Institut Teknologi Sepuluh Nopember, 2021)
Littering behavior studies are essential amid high waste conditions in Indonesia. This study aims to analyze changes in the student's littering behavior through a reinforcement program. Based on a case study at Junior High School in Depok, West Java, and use an explorative - qualitative approach, the study found that students' littering behavior can be categorized as active and passive. Active littering behavior in students is based on students' lack of concern for the environment due to a low knowledge of the impact of waste. Then passive littering behavior is caused by habits that delay littering even though they have an awareness of the waste dangers. Continuous reinforcement at school in positive and negative reinforcement can reduce student littering behavior, both actively and passively. The school's commitment to implementing environmental programs such as the